Evaluation of Microdesmis puberula Leaf Meal as Feed Ingredient in Laying Hen Diets - Esonu, B.O.; Azubuike, J.C.; Ukwu, H.O. (International Journal of Poultry Science, 2004)
A fifty-day feeding trial was conducted to evaluate the leaf meal of Microdesmis puberula as feed ingredient in laying hen diets. Microdesmis puberula is a preferred tropical browse plant. Seven experimental layers diets were formulated incorporating the leaf meal of Microdesmis puberula at 0.0, 2.5, 5.0, 7.5, 10.0, 12.5 and 15.0% dietary levels. One hundred and five (105), Shikka brown layers already 10 months in lay were divided into 7 groups of 15 birds each and randomly assigned to the 7 treatment diets in a completely randomized design (CRD). There were no significant differences (p